CORRELATION BETWEEN METACOGNITION ABILITY AND STUDENTS' SCIENCE PROCESS SKILLS ON CELLULAR BIOPROCESS MATERIALS - Maya Cindiati; S Suharsono; Dea Diella (Universitas Negeri Medan, 2021)
Metacognitive skills are required for students to manage and keep track of their understanding of fact-finding and concept-building by scientific process skills. This research aims to determine the correlation between metacognitive skills and students' scientific process skills on cell-based bioprocessing topics. The population of this study were all class of XI MIPA in one of SMA Negeri Kota Tasikmalaya. The research samples were 30 students from class XI MIPA 2 selected based on the purposive sampling method. The research instruments used contained an essay test consisted of 21 questions with indicators developed by Tawil and Liliasari to examine the scientific process skills. In contrast, the questionnaire adapted from the Metacognitive Awareness Inventory consisted of 50 positive statements with 4 Likert-scale-based alternative answers to examine the metacognitive skills. The normality and linearity test are conducted before performing the hypothesis test as a prerequisite. The hypothesis testing based on bivariate correlation and regression with an α of 0.05 showed a positive correlation between the two variables. The correlation coefficient with a value of 0.544 represents a moderate correlation between the two variables. The determination coefficient shows the contribution of 29.6% from the metacognitive skills in students' scientific process skills on cell-based bioprocessing topic.